Comparative and Historical Perspectives in Economic Sociology - Frank Dobbin (Journal of Economic Sociology, 2016)
This paper reviews historical and comparative theories in economic sociology that seek to explain substantial differences in economic behavior across time and space. In order to develop a more integrative analytical framework, one should avoid the stance of mainstream economics that states a force of self-interest determines economic behavior exogenously. The author challenges the idea of a universal economic system and shows that most sociologists share the view that a society’s structural, political, and cultural features shape economic behavior. However, scholars have not reached a consensus on a predominant explanation: some researchers focus on the role of social networks, others on power relations, and still others on social institutions-conventions. Originally, comparative and historical inquiry viewed these perspectives as alternative frameworks, but recent studies refer to them as complementary. Using the reasoning of three major predecessors to economic sociology — Karl Marx, Max Weber, and Emile Durkheim — the author categorizes modern comparative research in economic sociology in accordance with their theoretical toolkit. Despite all the differences, these studies apply the same inductive method, implying that a single process cannot account for variety in economic behavior.Journal of Economic Sociology offers the Russian translation of the paper which was first published in The Handbook of Economic Sociology (2005).